Subsoiling of an oxisol at fixed and varying depth in areas under sugarcane - Cortez, Lucas Aguilar [UNESP]; Marques Júnior, José [UNESP]; Peluco, Rafael Gonçalves [UNESP]; Siqueira, Diego Silva [UNESP]; Siansi, Frederico Luiz [UNESP]; Barbosa, Ronny Sobreira; Furlani, Carlos Eduardo Angeli [UNESP]; Camargo, Lívia Arantes [UNESP]; Silva, Laércio Santos [UNESP]; Gomes, Romário Pimenta [UNESP] (Springer Nature, 2020)
Knowledge of the spatial variability of compaction would minimize the movement of soil and optimize the operation and economic viability of sugarcane activities. The present study aimed to evaluate different protocols for soil loosening, using subsoiling at fixed and varying depths. The following four protocols were assessed: (i) total area subsoiling with a 7-shank sub-soiler at a fixed depth of 0.4 m in both row and inter-row zones; (ii) total area subsoiling with a 7-shank sub-soiler at varying depths in both row and inter-row zones; (iii) localized subsoiling with a 4-shank sub-soiler at a fixed depth of 0.4 m in a row; and (iv) localized subsoiling with a 4-shank sub-soiler at varying depths in a row. Soil resistance to penetration was measured at 111 sites within a 10 ha area, at a depth of 0.4 m. Data were subjected to descriptive and geostatistical analyses. Localized subsoiling at varying depths had an operational capacity 61.7% greater than the total area operation at a fixed depth. Moreover, along with producing a savings of 57.1% for diesel oil, the emission of equivalent CO2 was reduced by approximately the same amount. Mapping based on site-specific management presented good sustainability indicators, such as reduced energy consumption and lower CO2 emission.
Keywords: Soil compaction; Spatial variability; Sugarcane; Technology innovation